Availability of Digital Transformation Requirements and its Impact on the Quality of Hotel Services in the Gaza Strip: A Field Study - Abdelqader , Mansour; Hamdan, Muhammad (The Arab Journal of Administration, 2023)
The study aimed to measure the impact of digital transformation requirements on the quality of hotel services in the Gaza Strip, as the hotel sector has gained great importance in the Palestinian economy. The researchers have identified these requirements (strategy, organizational culture, human and material resources, and information infrastructure) to represent all the dimensions of the independent variable, while the dependent variable represented the dimensions of service quality, which have been addressed in previous related studies. The study included (7) hotels operating in the hotel and tourism sector in the Gaza Strip. The researchers used the descriptive-analytical method to interpret the phenomenon and the problem of the study, as well as designing a questionnaire tool to collect data from the studied community, in addition to conducting personal interviews with stakeholders. The total population size reached (70) individuals distributed among the hotels included in the study using the comprehensive survey method. The main results of the study shows that digital transformation requirements were available to a high degree with a relative percentage of (74.1%), and the found level of provided hotel services quality was estimated as a very high degree with a relative percentage of (88.4%). The results also showed a statistically significant impact of digital transformation requirements on the quality of hotel services. Additionally, the study’s results indicated low levels of digital information participation and the absence of digital culture dissemination. Among the most important recommendations are: developing the organizational structures of Palestinian hotels, working on diversifying hotel services and not limiting them to accommodation only, and urging hotel managers to enhance their role in developing the Palestinian services sector economy.